IMPROVING THE DIAGNOSIS, TREATMENT AND PREVENTION OF DISEASES OF THE ORAL MUCOSA IN CHILDREN - G’AFFOROVS, S.A. .; BAKAEV, J. N. (International Journal of Psychosocial Rehabilitation, 2020)
improving the system of providing dental care to the population in various countries and maintaining it at a decent level is an urgent problem, outlined by the modern approach of society to the issue of priority of preventive medicine (1, 4, 6, 7). Today, great importance is paid to improving the quality and accessibility of dental care to the population (2, 9, 10).